2020
DOI: 10.1556/2006.2020.00068
|View full text |Cite|
|
Sign up to set email alerts
|

The effects of parental control and warmth on problematic internet use in adolescents: A prospective cohort study

Abstract: Background and aimsProblematic internet use (PIU) is a highly prevalent condition with severe adverse effects. The literature suggests that parent-child bonding and parental behavioral control exert protective effects against PIU. However, the most relevant studies rely on simplistic measurement of parenting, cross-sectional designs and mixed-aged samples. Our study analyzed the effect of maternal and paternal parenting on PIU by using a prospective design and a cohort sample of same-aged children.MethodsData … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 36 publications
0
26
0
2
Order By: Relevance
“…In this context, many studies have reported the associations of low-quality parent–child relationships with children’s PIU [ 39 ]. In the parent–child relationship, children are prone to be more affected by parental warmth and responsiveness than adolescents [ 40 ]. Moreover, a mother’s parenting style influences the development and behaviors of a child more than fathers.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, many studies have reported the associations of low-quality parent–child relationships with children’s PIU [ 39 ]. In the parent–child relationship, children are prone to be more affected by parental warmth and responsiveness than adolescents [ 40 ]. Moreover, a mother’s parenting style influences the development and behaviors of a child more than fathers.…”
Section: Discussionmentioning
confidence: 99%
“…There is an ongoing debate as to the potential negative effects (e.g., sexual functioning problems) of pornography use in adults [10,18]. Although current studies suggested that a problematic use of pornography (PPU) develops in "only" up to 6% of pornography users, the lower age of users has been identified as a risk factor for PPU [11,12,19,20]. Moreover, it has been shown that the use of pornography influences both sexual attitudes and practices of adolescents [13,21].…”
Section: Discussionmentioning
confidence: 99%
“…In primary schools, only 3.4% of schools reported some cases; in older students, the problems were observed by 8.8%, respectively, 9.3% of SPS. Such low numbers did not correspond with the prevalence of screen-related pathological behaviors (e.g., problematic internet use, internet gaming disorder, cyber-bullying) in children and adolescents as estimated by studies conducted during the COVID-19 pandemic [2][3][4][5][6][7][8] or before [15][16][17][18][19][20][22][23][24][25][26][27]. This suggests that the ability of schools to detect problems is limited, at least in the situation of distant schooling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parental regulation of children use of media is very important given the fact that the new modern online media and online communication are nearly impossible to control by governments or by standard regulatory mechanisms [7]. Parenting in general, as a sum of practices and parental behavior toward a child, has been confirmed to affect many forms of adolescent risk or harmful behaviors (e.g., substance use, risky sexual behaviors, delinquency [8]), and also problematic internet use [9,10]. However, current evidence indicates that parenting strategies focused on media regulation (media parenting) are not very effective in preventing risky or problematic behaviors related to the use of media/screen-devices in children and adolescents [11][12][13].…”
Section: Introductionmentioning
confidence: 99%